2018
DOI: 10.3389/fnins.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Cerebral Syphilitic Gumma: A Report of Three Cases

Abstract: Cerebral syphilitic gumma is very rare and is often pathologically confirmed following surgery. This study reports three patients with cerebral syphilitic gumma. The first case was a 62-year-old man who was admitted to our hospital due to speech arrest for 10 hours. Head MRI showed a nodular signal shadow with a significant enhancement and a significant centerline shift. He subsequently received surgery, and cerebral syphilitic gumma was confirmed by postoperative pathology. The second patient was a 66-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…In most cases the lesions were multiple, with irregular enhancement and mild surrounding edema. 2,8 In our case there was a large area of edema around the lesion, which caused a space-occupying effect. The lesion showed uncommon ring enhancement, which is rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In most cases the lesions were multiple, with irregular enhancement and mild surrounding edema. 2,8 In our case there was a large area of edema around the lesion, which caused a space-occupying effect. The lesion showed uncommon ring enhancement, which is rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 55%
“…5 It has been established in the literature that syphilitic gumma could apparently be absorbed or could disappear after penicillin treatment. 2,8 Therefore, patients with cerebral syphilitic gumma can receive this diagnostic treatment to avoid unnecessary craniotomy. Penicillin treatment efficacy is measured indirectly by using serology, and a cure is usually defined as reversion to a negative serum status or a 4-fold reduction in the titer from an NTT.…”
Section: Fig 2 Histopathological Examination Showed a Large Quantitmentioning
confidence: 99%
“…Involvement of the brain parenchyma can manifest as brain atrophy, brain swelling, cerebral infarction, white matter lesions, [4] and cerebral syphilitic gumma. [5] This case presented with cerebral infarction, brain swelling, multiple cortical/subcortical regions of band-like hyperintensity, increased perfusion of the right hemisphere, and PAVF. Each of these findings could have arisen from another source; however, these were deemed unlikely because of a positive hemagglutination assay, confirming syphilis infection.…”
Section: Discussionmentioning
confidence: 99%
“…These can cause hydrocephalus or seizures, or may be incidental findings on brain imaging. 30,[63][64][65] The largest case series to date reported that 61.9% (13/21) of patients with CNS gummas who underwent lumbar puncture had a reactive CSF-VDRL. 63 Dementia paralytica presents as progressive dementia manifested as impaired memory and judgement followed by progressive disorientation, confusion, and occasional seizures.…”
Section: Clinicalmentioning
confidence: 99%